2007
DOI: 10.1159/000109502
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Incidence of Pediatric Medulloblastoma in the United States, 1995–2001

Abstract: Background/Aims: Brain tumors are the second most common pediatric malignancy. The literature suggests that one of the most common subtypes of malignant childhood brain tumor, medulloblastoma, has some seasonal variation in incidence by month of birth. Methods: Data from cases in the Central Brain Tumor Registry of the United States, including primary brain tumor cases diagnosed in children (0–19 years) between the years 1995 and 2001 from 13 state cancer registries, were analyzed to determine whether there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Astrocytoma showed a seasonal pattern in two studies (Heuch et al, 1998;McNally et al, 2002), and medulloblastoma seasonality by month of birth in three (Yamakawa et al, 1982;Heuch et al, 1998;Hoffman et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Astrocytoma showed a seasonal pattern in two studies (Heuch et al, 1998;McNally et al, 2002), and medulloblastoma seasonality by month of birth in three (Yamakawa et al, 1982;Heuch et al, 1998;Hoffman et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Examination of seasonal variation of birth in CNS tumours have had inconsistent results (Yamakawa et al, 1982;Heuch et al, 1998;Feltbower et al, 2001;McNally et al, 2002;Halperin et al, 2004;Hoffman et al, 2007), and overall, no seasonal pattern of birth is suggested. Seasonal variations sometimes seen for diagnostic subgroups were not consistent, so chance may have operated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a few studies indicate that exposure to infectious agents around the time of birth or in early childhood might modulate the risk for CNS tumours (Linet et al, 1996;Linos et al, 1998;Fear et al, 2001;McNally et al, 2002;Hoffman et al, 2007).…”
mentioning
confidence: 99%